Following control approach based on model predictive control for wheeled inverted pendulum robot. (18th March 2016) - Hirose, Noriaki; Tajima, Ryosuke; Koyama, Nagisa; Sukigara, Kazutoshi; Tanaka, Minoru
Abstract : Personal robots, which are seen as tools that will be needed to support our aging society, will be expected to support the comfortable lifestyles of healthy young people as well as the elderly. However, excessive and premature robot support may adversely impact the physical abilities of their human owner/operators. In this paper, the authors propose a personal robot equipped with wheeled inverted pendulum control that can carry baggage and follow the human being. Since such robots could remove the drudgery associated with carrying luggage, their use could also encourage people to go outside and walk briskly, which could contribute to improved health management. This paper proposes a novel control approach for a robot following the human being. The proposed approach employs a model predictive control that facilitates consideration of several types of upper and lower level constraints a personal robot would require. The effectiveness of our proposed approach was then verified in experiments using a prototype personal robot. Graphical Abstract: